2010
DOI: 10.3732/ajb.0900237
|View full text |Cite
|
Sign up to set email alerts
|

The importance of soil microorganisms for maintaining diverse plant communities in tallgrass prairie

Abstract: Widespread microbially mediated negative feedback indicates that plant community diversity and composition in tallgrass prairie are dependent on soil microorganisms. Native soil microorganisms should be considered in restoration efforts of tallgrass prairie and, potentially, other native plant communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 54 publications
(65 reference statements)
1
38
0
1
Order By: Relevance
“…There are both positive and negative soil community feedback activities playing crucial roles in the establishment of plant population structure. Some studies have demonstrated the inevitable role of certain endosymbionts (either arbuscular mycorrhizal fungi or diazotrophs) in the initial establishment of species in a new environment or community conversion due to positive feedback, but likely leading to exotic species dominance instead of establishing a diverse plant community (Rejmanek and Richardson, 1996;Larson and Siemann, 1998;Klironomos, 2002;Fitzsimons and Miller, 2010). However, this positive feedback will have a potential role to play in an agricultural system, where single monoculture crops are used instead of a diverse species population.…”
Section: Alteration In Root Secretionsmentioning
confidence: 98%
See 2 more Smart Citations
“…There are both positive and negative soil community feedback activities playing crucial roles in the establishment of plant population structure. Some studies have demonstrated the inevitable role of certain endosymbionts (either arbuscular mycorrhizal fungi or diazotrophs) in the initial establishment of species in a new environment or community conversion due to positive feedback, but likely leading to exotic species dominance instead of establishing a diverse plant community (Rejmanek and Richardson, 1996;Larson and Siemann, 1998;Klironomos, 2002;Fitzsimons and Miller, 2010). However, this positive feedback will have a potential role to play in an agricultural system, where single monoculture crops are used instead of a diverse species population.…”
Section: Alteration In Root Secretionsmentioning
confidence: 98%
“…In contrast, through negative feedback, the remnant whole-soil microbial communities from native ecosystems can help achieve the restoration of native plant communities. The plant diversity was well restored in a tallgrass prairie by microbia-mediated negative feedback from native plant soil (Fitzsimons and Miller, 2010). However, a separate study explored the microbial community structure and composition (Rosenzweig et al, 2013), and there were no connective studies between the soil microbiome and ecological restoration projects.…”
Section: Alteration In Root Secretionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil microbes have been considered as drivers of plant diversity and productivity in terrestrial ecosystems (van der Heijden et al 2008). Although much of the work on plant/microbe interactions has been carried out in herb-dominated ecosystems (e.g., McCulley and Burke 2004, Kaye et al 2005, Fitzsimons and Miller 2010, Marshall et al 2011), increasingly such studies are being carried out also in forests (Eisenlord and Zak 2010). Eisenhauer et al (2011) found significant positive relationships between soil biota and herb layer diversity of a temperate hardwood forest in Canada; however, they did so by assessing only microbial biomass and basal metabolism, neither examining microbial community composition nor employing multivariate ordination techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, field-scale experiments have shown that cultivated fields undergoing restoration can benefit greatly by inoculation with soil collected from established native prairie [49,50]. This technique first appeared in the literature at the time prairie restoration was nearly complete at Glacial Ridge, and therefore not attempted.…”
Section: Nearby Prairie Remnantsmentioning
confidence: 99%